'How are we going to do it?' An exploration of the barriers to access to higher education amongst young people from disadvantaged communities. Issue 3 (3rd July 2019) - Scanlon, Margaret; Jenkinson, Hilary; Leahy, Pat; Powell, Fred; Byrne, Olive
Abstract : The number of young people progressing to higher education (HE) in Ireland has grown significantly over the last three decades but inequality of access and participation remain a major policy challenge. This article sets out to explore the factors which impact on levels of participation in HE by young people from lower socio-economic backgrounds, based on interviews and focus groups with 70 secondary school students and 25 parents in three case-study locations. In line with previous research, we found that financial considerations continue to have an important influence on decisions about whether to go on to higher education. The findings in relation to young people's aspirations and orientations to HE present a more complex picture. While the majority of students aspired to go on to HE, this was countered by a lack of confidence in relation to certain aspects of college life, both social and academic.